Język protokołów z posiedzeń Towarzystwa Polskich Rzemieślników w Zielonej Górze = Language of protocols of the meetings of Association of Polish Craftsmen in Zielona Góra - Żuraszek-Ryś, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of description in this article is the language and methods of its use by a specific community - Polish society inhabiting the German city Grunberg, today`s Zielona Gora, at the turn of the 19th/20th centuries. The research material consists of the protocols from the meetings of Association of Polish Craftsmen in Zielona Gora - socio-cultural association which used to deal with organization of lectures and readings broadening the knowledge abort Poland and known Poles, Polish language courses, as well as many other initiatives aiming at promoting and care for Polish traditions and Polish language.
Keywords: wspólnota komunikatywna; protokół; styl urzędowy; Towarzystwo Polskich Rzemieślników; Zielona Góra; communicative community; protocol; official style; Association of Polish Craftsmen